IDENTITAS KEINDONESIAAN DALAM DRAMA NYANYI SUNYI REVOLUSI KARYA AMIR HAMZAH - Rahayu, Lina Meilinawati (Diksi, 2020)
(Title: Indonesian Identity in Drama's Nyanyi Sunyi Revolusi by Amir Hamzah).This paper will examine the beginning period of Indonesia which is represented in the drama. The past events which occurred more than seventy years ago are now retold, not only to re-establish who Amir Hamzah was, but also to explain the Indonesian identity and the roles he played in building a nationality. Amir Hamzah, one of the great authors of Indonesia who also contributed in formulating the archipelago as Indonesia, who advocated Malay language as the language of unity of Indonesia, should be killed by several young men because he was a sultan's nephew. Those young men considered the Sultans and their families as Dutch henchmen. The tragic story of Amir Hamzah's life was staged in a drama titled "Nyanyi Sunyi Revolusi" (trans. The Quiet Singing of Revolution)which with the scripts was written by Ahda Imran. Socio-political conditions give rise to the need to define "˜self'. This requires serious rethinking. This drama also illustrates the identity of Indonesia after independence. In other words, literature describes history from a different view. By using the principle of New Historicism, this paper will explain the complex problem that occurred in Indonesia after independence until the 50s. Besides, it also will describe "Indonesian Identity" in the drama "Nyanyi Sunyi Revolusi". In this context, Indonesian literary texts which reflect Indonesian history can be positioned as historical reading from a different version.Keywords: identity, Indonesian, revolution, new historicism.